8(z-6)+7z-1=

Simple and best practice solution for 8(z-6)+7z-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(z-6)+7z-1= equation:


Simplifying
8(z + -6) + 7z + -1 = 0

Reorder the terms:
8(-6 + z) + 7z + -1 = 0
(-6 * 8 + z * 8) + 7z + -1 = 0
(-48 + 8z) + 7z + -1 = 0

Reorder the terms:
-48 + -1 + 8z + 7z = 0

Combine like terms: -48 + -1 = -49
-49 + 8z + 7z = 0

Combine like terms: 8z + 7z = 15z
-49 + 15z = 0

Solving
-49 + 15z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + 15z = 0 + 49

Combine like terms: -49 + 49 = 0
0 + 15z = 0 + 49
15z = 0 + 49

Combine like terms: 0 + 49 = 49
15z = 49

Divide each side by '15'.
z = 3.266666667

Simplifying
z = 3.266666667

See similar equations:

| 12x-4e^5= | | 2-3x=2+4x | | ((2*t)/15)-(((3*t)-5)/20)=((t/5)-3) | | 14t-33=14t-8 | | 6(x-4)=-4 | | 56=71 | | 4e^5= | | 4e^5=x | | -2x+y=3y-6x | | 20x+5y=285 | | 3(y-1)=c | | 8x^2(4x^3+2x^2+3x+1)= | | -7(3x-4)=-49 | | 6(2x-1)=4x+18 | | (X-2)(x+6)=180 | | -3(1+5)+4=-104 | | 3-x/42 | | 5/7-3Y=-2 | | 6-5[4-(7y-2)]= | | -(2+x)=-3(x-2) | | -6(n+-2)+4(3+-6x)=-36 | | y=(x+9)m | | 4X^3/X^5=64 | | -6(n+-2)+4(3+-6x)=36 | | 2ln(x+2)=ln(x-1) | | 5f+7f+f= | | Y/85=6/10 | | .25x+.10y=2.85 | | 200x-.67=100x+81 | | 7n+16-5n=34 | | 5/2h15 | | r-1.2=11.5 |

Equations solver categories